Impact of the growing use of narrative verdicts by coroners on geographic variations in suicide: analysis of coroners' inquest data. - Carroll, R; Hawton, K; Kapur, N; Bennewith, O; Gunnell, D (2012)
BACKGROUND: Coroners' death certificates form the basis of suicide statistics in England and Wales. Recent increases in coroners' use of narrative verdicts may affect the reliability of local and national suicide rates. METHOD: We used Ministry of Justice data on inquests held between 2008 and 2009 and Local Authority suicide data (2001-02 and 2008-09) to investigate variations between coroners in their use of narrative verdicts and the impact of these on suicide rates, using 'other' verdicts (79% of which are narratives) as a proxy for narrative verdicts. RESULTS: There was wide geographic variation in Coroners' use of 'other' (mainly narrative) verdicts--they comprised between 0 and 50% (median = 9%) of verdicts given by individual coroners in 2008-09. Coroners who gave more 'other' verdicts gave fewer suicide verdicts (r = - 0.41; P < 0.001). In the 10 English Coroners' jurisdictions where the highest proportion of 'other' verdicts were given, the incidence of suicide decreased by 16% between 2001-02 and 2008-09, whereas it did not change in areas served by the 10 coroners who used narratives the least. CONCLUSIONS: Variation in Coroners' use of narrative verdicts influences the validity of reported regional suicide rates. Small-area suicide rates, and changes in these rates over time in the last decade, should be interpreted with caution.